2021
DOI: 10.1080/08880018.2021.1973628
|View full text |Cite
|
Sign up to set email alerts
|

ABCC4, ITPA, NUDT15, TPMT and their interaction as genetic predictors of 6-mercaptopurine intolerance in chinese patients with acute lymphoblastic leukemia

Abstract: Supplemental Figure.1. 6-MP Dose Intensity in Patients with both ABCC4 c.912G>T and ITPA c.94C>A variants. 6-MP dose intensity were compared in patients with (n=11) and without both variants (n=134) using Mann Whitney U test. "+" indicates mean values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“… 26 , 41 Three studies defined hepatotoxicity as ALT >500 U/L, ALT >700 U/L, and ALT or AST >500 U/L, respectively. 25 , 40 , 44 The remaining two defined hepatotoxicity as the highest direct bilirubin values ≥1.5 mg/dL, and as either ALT, AST, alkaline phosphatase or total bilirubin above 2-fold upper limit of normal, respectively. 39 , 52 All above-mentioned information are listed in Online Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 41 Three studies defined hepatotoxicity as ALT >500 U/L, ALT >700 U/L, and ALT or AST >500 U/L, respectively. 25 , 40 , 44 The remaining two defined hepatotoxicity as the highest direct bilirubin values ≥1.5 mg/dL, and as either ALT, AST, alkaline phosphatase or total bilirubin above 2-fold upper limit of normal, respectively. 39 , 52 All above-mentioned information are listed in Online Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no significant difference in the incidence of hepatotoxicity (OR=2.43, 95% CI: 0.95-6.20; P =0.06) ( Figure 4C ) was observed in the recessive model either. 25 , 39 , 41 , 44 Three studies comprising 426 ALL patients were included to compare the events of hepatotoxicity in NUDT15 c.52 G>A variant carriers (GA+AA) versus wild-type patients (GG) and the result indicated that there was no significant difference in hepatotoxicity incidence in either (OR=1.09, 95% CI: 0.22-5.31; P =0.91) ( Figure 4D ). 25 , 41 , 44 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the pharmacogenomics of the ABCC4 gene, the association of certain variants with 6-mercaptopurine intolerance has been described in Chinese children with ALL, while an association with hematologic toxicity was found in an Egyptian population with ALL ( 35 , 36 ). Similarly, we found a risk association between high-grade hematologic adverse events and the ABCC4 rs2274409 variant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ALL patients with intermediate active NUDT15 and ABCC4 variants experienced higher 6-MP intolerability, compared with the group with either of the variants ( Tanaka et al, 2018 ). In a very recent study, the co-occurrence of the ABCC4 (c.912G > T, rs2274407) and ITPA (c.94C > A) variants in 145 Chinese children with ALL witnessed a significant positive association with 6-MP intolerance ( Fan et al, 2022 ). Meanwhile, ABCC4 c.2128G > A (rs3765534) carriers experienced a significant increase in the DNA-TG to 6-MP dose ratio, which was associated with a high risk of leukopenia ( Fan et al, 2022 ).…”
Section: Pharmacogenetics Of Thiopurinesmentioning
confidence: 99%
“…In a very recent study, the co-occurrence of the ABCC4 (c.912G > T, rs2274407) and ITPA (c.94C > A) variants in 145 Chinese children with ALL witnessed a significant positive association with 6-MP intolerance ( Fan et al, 2022 ). Meanwhile, ABCC4 c.2128G > A (rs3765534) carriers experienced a significant increase in the DNA-TG to 6-MP dose ratio, which was associated with a high risk of leukopenia ( Fan et al, 2022 ). Similarly, ABCC4 SNP rs2274407 was found to be related to the increased 6-TGN to 6-MP dose ratio ( Choi et al, 2019 ).…”
Section: Pharmacogenetics Of Thiopurinesmentioning
confidence: 99%